Evaluation of resistance pattern of the multi-drug resistant (MDR) bacteria isolated from burn wounds (Stamford Journal of Microbiology, 2015)
Out of 10 random burn wound swab samples, 15 isolates were found which included Staphylococcus aureus, Klebsiella pneumoniae, Bacillus cereus, Shigella spp. Pseudmonas aeruginosa, Citrobacter spp. and Escherichia coli. Antibiogram assay revealed that four of them were multi-drug resistant (MDR) strains, i.e, Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa and E. coli which were further selected for a comparative analysis of resistance through determining minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) by using chloramphenicol and tetracycline. In case of tetracycline, the highest MIC value was estimated to be 30 ?g/ml and the highest MBC value was found to be 60 ?g/ml for the 4 MDR strains tested. Whereas, against chloramphenicol, the highest MIC value was 62.5 ?g/ml and the highest MBC value was 125 ?g/ml for all the MDR strains except for E. coli, which exhibited absolute resistance. DOI: http://dx.doi.org/10.3329/sjm.v3i1.22744 Stamford Journal of Microbiology, Vol.3(1) 2013: 6-8